2
$\begingroup$

Suppose that $\sum_{j=1}^\infty a_j$ is conditionally convergent. Use the partial sum formula to show that $$\sum_{j=1}^\infty j^{\frac{1}{j}}a_j$$ is also convergent.

Any hints on how to get started?

$\endgroup$
5
$\begingroup$

Let $b_j = j^{1/j}$. The sequence $b_j$ is bounded and decreasing (when $j > 2$) with $b_j \to 1$. The sequence of partial sums $S_n = \sum_{j=1}^n a_j$ is convergent and, hence, bounded.

We have convergence of the telescoping series

$$\sum_{j=1}^n (b_j - b_{j+1}) = b_1 - b_{n+1},$$

I'll leave it to you to show that this implies absolute convergence of

$$\sum_{j=1}^n S_j(b_j - b_{j+1}). $$

Summation by parts (another detail for you) gives

$$\sum_{j=1}^n a_j b_j = S_nb_{n+1} + \sum_{j=1}^nS_j(b_j - b_{j+1}) .$$

Since both terms on the RHS converge so too does the sum on the LHS.

A question for you to consider is where did we use the fact that $b_j$ is eventually decreasing.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.